Youtube’s Home Page: Senses of Brazilianities Configured by the Platform (Intercom - Brazilian Journal of Communication Sciences, 2024)
The article proposes a reflection on the ways in which senses of national identity are configured within the boundaries of YouTube interfaces, specifically focusing on Brazilian identities. To do so, we analyze the platform’s home page, its algorithms, settings, and user interface using Kilpp’s (2003) frames methodology. The dissection of these territories allows us to deconstruct the meanings attributed to Brazil, Brazilians, and certain Brazilianities inherent to this media, as well as to identify some of the imaginaries invoked in constructing these meanings. The text pays special attention to the home page, considering it a central space for understanding the platform’s assemblages and the dynamics of contemporary technoculture from which it emerges.
Keywords: Home Page; YouTube; Brazilianities; Imaginaries; Audiovisual.